Sarcoma of the heart: a rare intracardiac tumor and review of literature - Mohtarrudin, Norhafizah; Mohd Dusa, Noraini; Sakr, Ahmad; Mohd Sidik, Shiran; Mohd Ali, Razana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Primary sarcomas of the heart are exceptionally rare and are aggressive tumours. We report a 38 year old Chinese lady who had an intermediate grade sarcoma with myofibroblastic differentiation. The tumour was found in the right atrium. Literature reviews of rare intracardiac sarcomas are discussed.